Energy analysis of two stage packed-bed chemical looping combustion configurations for integrated gasification combined cycles. (1st June 2015) - Hamers, H.P.; Romano, M.C.; Spallina, V.; Chiesa, P.; Gallucci, F.; van Sint Annaland, M.
Abstract: Chemical looping combustion is a promising technology for power production with integrated CO2 capture. High overall efficiencies can be reached, if the CLC reactors are operated at elevated pressures and high temperature, which can be accommodated in packed bed reactors. More possible oxygen carriers can be selected if the desired temperature rise for power production is achieved in a two stage chemical looping combustion (TS-CLC) process. In this work, the TS-CLC configuration using copper and manganese based oxygen carriers has been integrated in a complete power plant based on coal gasification (IG-CLC). An extensive energy analysis based on the combined use of a packed bed reactor modeling tool and a complete process simulation has been undertaken. An economic estimation of the reactors capital cost has also been carried out. From the material and energy balances the IG-CLC with one stage nickel-based CLC process results in a net electric efficiency of 41.1% on low heating value basis. In case of TS-CLC, efficiencies of 40.3%–40.8% have been obtained. This demonstrated that IGCC (integrated gasification combined cycles) adopting a TS-CLC process can also achieve high efficiency compared to conventional CO2 capture technologies. Although a larger reactor volume is required for TS-CLC, the total estimated investment costs are a factor two lower, because the oxygen carriers are much cheaper. Highlights: Complete IG-CLC power plants have been evaluated for different CLC configurations. Novel operation strategy for the TS-CLC has been proposed: TS-CLC parallel. The estimated capital costs of TS-CLC are a factor two smaller than one stage CLC. The process efficiency of TS-CLC is demonstrated to be close to the one stage CLC.